2018
DOI: 10.1016/j.neuroscience.2018.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Expression Profiles of Metallothionein I/II and Megalin in Cuprizone Model of De- and Remyelination

Abstract: Copper chelator cuprizone (CPZ) is neurotoxicant, which selectively disrupts oligodendroglial respiratory chain, leading to oxidative stress and subsequent apoptosis. Demyelination is, however, followed by spontaneous remyelination owing to the activation of intrinsic CNS repair mechanisms. To explore the participation of metallothioneins (MTs) in these processes, in this study we analyzed the expression profiles of MT-I/II and their receptor megalin (low-density lipoprotein receptor related protein-2) in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 88 publications
2
20
0
Order By: Relevance
“…More recently, several studies indicated that extracellular MTs can bind to multiligand scavenger receptor megalin, also known as low-density lipoprotein receptor-related protein-2 (LRP-2) and gp330 [ 23 , 24 ]. It is thought that resulting membrane complex MT-megalin could either trigger pro-survival and pro-mitotic pathways via protein kinase B (PKB, AKT-1) activation through SH2/SH3 domains or/and undergo endocytic internalization regulated by NPXY sequences, thereby supplying the cell with “exogenous” MTs, that may be even directly shuttled into the nucleus upon endocytosis [ 25 , 26 , 27 , 28 , 29 ]. Apart from that, upon ligand binding, megalin can be, as with Notch, subjected to regulated intramembrane proteolysis (RIP) resulting in cleavage and release of C-terminal soluble megalin intracellular domain (LRP-2-ICD; MICD), which consequently enters the cell nucleus where directly modifies gene expression [ 30 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, several studies indicated that extracellular MTs can bind to multiligand scavenger receptor megalin, also known as low-density lipoprotein receptor-related protein-2 (LRP-2) and gp330 [ 23 , 24 ]. It is thought that resulting membrane complex MT-megalin could either trigger pro-survival and pro-mitotic pathways via protein kinase B (PKB, AKT-1) activation through SH2/SH3 domains or/and undergo endocytic internalization regulated by NPXY sequences, thereby supplying the cell with “exogenous” MTs, that may be even directly shuttled into the nucleus upon endocytosis [ 25 , 26 , 27 , 28 , 29 ]. Apart from that, upon ligand binding, megalin can be, as with Notch, subjected to regulated intramembrane proteolysis (RIP) resulting in cleavage and release of C-terminal soluble megalin intracellular domain (LRP-2-ICD; MICD), which consequently enters the cell nucleus where directly modifies gene expression [ 30 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to antioxidant effects, MTs are considered reactive proteins that possess neuroprotective and regenerative effects [ 20 ]. In a mouse model of cuprizone-induced neurotoxicity, the expression levels of MT1/MT2 and megalin were increased in certain brain regions [ 21 ]. Thus, the increased expression of megalin and MT1A and MT2A ligands can induce oxidative and inflammatory responses in KM rats; in the present study, this was reversed in KM + FM rats by blocking the signaling cascades of the androgen receptor, megalin, and MT1A.…”
Section: Discussionmentioning
confidence: 99%
“…Copper chelator CPZ is neurotoxicant, which selectively disrupts the respiratory chain of oligodendrocyte, leading to oxidative stress and subsequent apoptosis 17. CPZ-treated animals are well-accepted demyelination models that could induce schizophrenia-like behaviors including memory impairment, and thus, it can be used to induce mouse demyelination model of schizophrenia 8,14,16.…”
Section: Discussionmentioning
confidence: 99%